Feherty : the remarkably funny and tragic journey of golf's David Feherty - Feinstein, John (Hachette Books, 2023)
"The definitive biography of enigmatic golfer, commentator, and performer David Feherty--one of the most universally beloved figures in the game. John Feinstein, who has spent four decades finding intriguing sports characters and narratives and turning them into classic books, chronicles the life and career of David Feherty. The two have known each other for years, beginning with Feinstein's work on A Good Walk Spoiled, researched and written at a time when Feherty was an excellent player, who won five times in Europe and was on the '91 Ryder Cup team, but also a functioning alcoholic. In retirement from the game, Feherty has sobered up, while his golf world persona has only grown in stature. Feherty is now a grand ambassador for golf, a man who is feted by US Presidents and respected by every big name in the game. Feinstein tells hilarious true tales about Feherty's time in the limelight and interactions with stars such as Tiger Woods, Rory McIlroy, Payne Stewart, and Seve Ballesteros. He also details Feherty's struggles with alcoholism, the death of his son who was lost to addiction, and the highs and lows of Feherty's marriages. Feinstein captures the human being behind the athlete, and his triumphant rebound as a golf commentator after his athletic career fell apart. Feherty is fall-down-funny, self-deprecating, and a lifelong underdog who has thrived as a commentator and television interview host, and most recently as a touring standup comic, using the difficult experiences of his life as a source for humor and understanding, which Feinstein mines with an expert's touch."--Publisher.